MAKNA SIMBOLIK DAN NILAI ESTETIKA SENI HIAS DAN TATA LETAK PURA JAGATNATHA DI JEMBRANA BALI: DALAM KONTEKS KEHIDUPAN KERAGAMAN MASYARAKAT HINDU BALI - I Ketut Sunarya (Universitas Trisakti, 2012)
Abstract The art of decoration of Pura Jagatnatha that was found in Jembrana bali was an aesthetical symbol that made the pura which the meaning was a mount interpreted as source of prosperity. Its display created some questions of philosophical concepts of art decoration, glory, unique, and characteristic, and relation between the setting of pura and the real life of Balinese Hindu people. Pura describes three peaks of the big time of Balinese art of decoration; ancient Bali with the Balinese Character, the big time of Gelgel kingdom with its calsical things, and the currentcharacter with its Western influences. The art of decoration of pura have the aesthetical principles, function, related to personal, social, and physical functions. Style was related to formal arrangement that consisted of intelectual, biomorphical, and aesthetical arrangements. Fantasy style was related to the divinities, folklores, and stories of giants world. The meaning assesment told that Balinese refractional bias of Pura Jagatnatha was beautiful and had the core of symbolic meaning AbstrakSeni hias pura Jagatnatha di Jembrana Bali adalah simbol estetik yang menjadikan pura bermakna gunung sebagai sumber kesuburan. Tampilan yang memunculkan pertanyaan tentang konsep filosofi seni hias, kemegahan, keunikan, dan karakteristik, serta hubungan tata letak pura dengan kehidupan masyarakat Hindu Bali. Pura menggambarkan tiga puncak kejayaan seni hias Bali, yakni masa Bali kuno sampai diketemukan karakter kebalian, masa keemasan kerajaaan Gelgel dengan klasiknya, dan karakter kekinian dengan pengaruh baratnya. Seni hias pura berpegang pada prinsip estetika, yakni : fungsi, menyangkut personal, fungsi sosial dan fungsi fisik. Gaya , menyangkut gaya sususnan formal, yakni susuanan intelektual, biomorfis, dan gaya susunan estetik. Gaya fantasi menyangkut cerita kadewatan, cerita rakyat, dan dalam alam buta . Kajian makna menyebutkan bahwa seni bias Pura Jagatnatha Bali selain indah makna simbolik menjadi inti pura tersebut.